Extremely large, linear, and controllable positive magnetoresistance in neodymium-doped graphene foam for magnetic sensors. (September 2021) - Sagar, Rizwan Ur Rehman; Zaiping, Xu; Iqbal, Javed; Rehman, Sajjad Ur; Ashraf, Hamad; Liu, Chao; Zeng, Jinming; Liang, Tongxiang
Abstract: Strain engineering of graphene is a widely researched topic of the decade, one can realize the unique applications of graphene due to the strain affect. Doping in graphene is one of the methods to introduce strain and rare earths (RE) doping in graphene is a challenging task as the size of RE-atoms is much bigger compared to carbon. Herein, neodymium (Nd) is doped in graphene foam (GF) successfully, with the help of double-zone chemical vapor deposition (CVD) at hollow sites (interstitial doping). The doping is confirmed from several characterization tools and magnetotransport properties are detected afterword's. An extremely large positive magnetoresistance (PMR ∼ 1410% at 5 K under 8 T applied magnetic field) is observed in Nd-doped GF compared to as-grown GF (PMR ∼ 250% at 5 K under 8 T applied magnetic field). The PMR afterward starts decreasing upon the fabrication of Nd-composite at high temperature ∼1400 °C. Technologically, topological band structure of graphene upon doping influences the path of charge carriers as a result, a change in fermi-surface occurs, due to which unique applications can be realized. Graphical abstract: Image 1 Highlights: Fabrication of Nd-doped Graphene Foam (GF) and Nd-GF composites via specially designed double-zone CVD system. Fabrication of ball-like and fiber-like special morphologies of neodymium (Nd) on the surface of graphene. Magnetotransport properties of Nd-doped GF and Nd-GF composites are detected. A large positive magnetoresistance (PMR ∼ 1410 % at 5 K under 8 T applied magnetic field) of Nd-doped GF is detected. Magnetic sensors can be realized with the help of Nd-doped GF samples due to large PMR.